2011
DOI: 10.1021/ie102330d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas–Solid Hydrodynamic Behavior on the Reactions of the Sorption Enhanced Steam Methane Reforming Process in Bubbling Fluidized Bed Reactors

Abstract: A three-dimensional two-fluid modeling approach with the kinetic theory of granular flow was used to study the process of sorption enhanced steam methane reforming (SE-SMR) carried out in a bubbling fluidized bed reactor. The effects of the superficial gas velocity and restitution coefficient on the solid flow pattern and reactions were investigated. The hydrodynamic properties of the reactive flow showed different behaviors compared to the cold flow. The superficial gas velocity and restitution coefficient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Adopting a three‐dimensional two‐fluid KTGF model, Wang et al . showed that the hydrodynamic properties of the reactive flow showed different behaviours compared to the cold flow.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adopting a three‐dimensional two‐fluid KTGF model, Wang et al . showed that the hydrodynamic properties of the reactive flow showed different behaviours compared to the cold flow.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, still the conventional two-fluid modelling framework is very crude. Adopting a three-dimensional two-fluid KTGF model, Wang et al [20] showed that the hydrodynamic properties of the reactive flow showed different behaviours compared to the cold flow. Hence, extensive fitting of the model to cold-flow experimental data may not be reasonable if the model is intended for prediction of the chemical reactor performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bubbling fluidized bed reactors are widely used in many industrial processes such as combustion, gasification, catalytic reforming, and drying. Bubbles are regarded as the typical structures in a bubbling fluidized bed, which significantly affect the hydrodynamics, heat, and mass transfer behaviors as well as reaction performance . In the last decades, bubble characteristics in a gas–solid fluidized bed have been widely explored. , Some classic theories and models have been put forward and applied in the prediction of industrial systems, such as the models of a single rising bubble or bubbles in a freely bubbling fluidized bed …”
Section: Introductionmentioning
confidence: 99%